The importance of gut health in early life for long term health - Kadim, Muzal; Masita, Bertri Maulidya (World Nutrition Journal, 2022)
Introduction. The gut microbiota plays an important role in the normal functioning of the host organism. The microbiota of healthy newborn affected by many factors such as prenatal exposures, maternal nutrition, mode of delivery, type of feeding, introduction to solid food and its type, geography, and antibiotics consumption; and its composition continues to mature until reaching 3 years of age. Normal gut microbiota is essential in gut health, and play an important role in our homeostasis. Therefore, gut microbiota is considered a crucial factor for proper early life development and lifelong health. Prebiotics, along with probiotics, may alter gut microbiota composition thus play a role in the prevention of various diseases associated with dysbiosis condition. Methods. Advanced search for relevant literatures in PubMed, Cochrane, and Willey was conducted. After assessing the relevancy and eligibility, articles were selected and critically appraised. Conclusions. Accumulating evidence from different studies has shown that the occurrence of a disease is often preceded by early alterations of the microbiota. Many studies established correlation between gut microbiota dysbiosis with diseases pathogenesis i.e obesity and other metabolic syndrome, asthma and allergies, also stress-related disorder. Prebiotic supplementation has proven to be effective in obesity, asthma and allergies management, also beneficial for immune system.